SERUM URIC ACID LEVELS APPEAR TO PREDICT IN-HOSPITAL MORTALITY IN PATIENTS ADMITTED WITH ACUTE ISCHEMIC STROKE. (June 2022) - Tsankof, Alexandra; Valanikas, Evripidis; Papathanasiou, Erofili; Polychronopoulos, Georgios; Papadopoulos, Anastasios; Tzavelas, Marios; Satsoglou, Sarantis; Veneti, Stavroula; Ztriva, Eleftheria; Tziomalos, Konstantinos
Abstract : Objective: Previous studies reported discrepant results regarding the association between serum uric acid levels and the outcome of acute ischemic stroke. We aimed to evaluate this association. Design and method: We prospectively studied 1, 107 consecutive patients who were admitted for acute ischemic stroke (42.1% males, age 79.8 ± 7.2 years). Stroke outcome was evaluated with dependency at discharge (modified Rankin scale (mRS) at discharge 2–5) and with in-hospital mortality. Stroke severity was evaluated at admission with the National Institutes of Health Stroke Scale (NIHSS). Serum uric acid levels were measured at the second day after admission in the fasting state. Results: Serum uric acid levels did not correlate with the mRS at discharge (r = 0.003, p = NS) and did not differ between patients who were dependent at discharge and those who were independent (5.7 ± 1.9 and 5.8 ± 1.7 mg/dl, respectively; p = NS). Independent predictors of dependency were age (relative risk (RR) 1.075, 95% confidence interval (CI) 1.043–1.107, p < 0.001), history of ischemic stroke (RR 2.201, 95% CI 1.482–3.270, p < 0.001), family history of cardiovascular disease (RR 1.978, 95% CI 1.166–3.358, p < 0.05) and NIHSS at admission (RR 1.421, 95% CI 1.334–1.514, p < 0.001). Serum uric acid levels were higher in patients who died during hospitalization than in those who were discharged (6.2 ± 2.0 and 5.7 ± 1.9 mg/dl, respectively; p < 0.05). Independent predictors of in-hospital mortality were atrial fibrillation (RR 2.015, 95% CI 1.083–3.747, p < 0.05), diastolic blood pressure at admission (RR 1.046, 95% CI 1.024–1.068, p < 0.001) and NIHSS at admission (RR 1.188, 95% CI 1.148–1.231, p < 0.001). Conclusions: Elevated serum uric acid levels might be associated with higher in-hospital mortality in patients admitted with acute ischemic stroke.